An Analysis of Argument Structure of Research Article of English Postgraduate Program of Bengkulu University Published In Journal - Resakti Alamsyah Bermani; Safnil Safnil; Arono Arono (JOALL (Journal of Applied Linguistics and Literature), 2017)
This study investigates the argument pattern in research articles by postgraduate students of English and Education University Bengkulu, based on Toulmin’s Theory (1958). This study analyzed the argument pattern, and reveal the type of data used by the student to support the claim in their argument contains in introduction section and discussion section of Journal Applied Lingusitic and Literature (JOALL) 2016. The data analysis result show that (a) the common argument pattern employed for arguments in introduction section of Research Article published in JOALL is Semi-complete pattern; (b) in discussion section the authors also commonly employ Semi-complete pattern. In addition (c) there are five types of data used by the authors to ground their arguments they are, Facts, Statistics, Example, Expert Opinion, and A Note on Visual. It can be conclude that the Research Article author published in JOALL have a good argumentative text based on Toulmin’s theory.